2019
DOI: 10.1016/j.jsxm.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Brain Subcortical Network Topology Between Men with and Without PE: A Diffusion Tensor Imaging Study

Abstract: Introduction Premature ejaculation (PE) is a highly prevalent male sexual dysfunction. Previous studies have found abnormal activity in the sympathetic nervous system and penile sensory pathway of PE. Few studies have investigated the neural mechanisms underlying PE. Aim The aim of this study was to examine whether the altered cortico-subcortical network topological properties of the brain white matter structural network coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Compared with HC, nsPE patients showed less aberrant brain regions than sPE patients, which were located in DMN (the left median cingulate and paracingulate gyri and right superior frontal gyrus, orbital part) and AN (the left superior parietal gyrus). Decreased shortest path length was found in the superior frontal gyrus (medial orbital) of PE in our diffusion tensor imaging (DTI) study 36 . In addition, previous fMRI study shows that decreased intrinsic activity was found in the orbitofrontal cortex of PE patients 43 .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Compared with HC, nsPE patients showed less aberrant brain regions than sPE patients, which were located in DMN (the left median cingulate and paracingulate gyri and right superior frontal gyrus, orbital part) and AN (the left superior parietal gyrus). Decreased shortest path length was found in the superior frontal gyrus (medial orbital) of PE in our diffusion tensor imaging (DTI) study 36 . In addition, previous fMRI study shows that decreased intrinsic activity was found in the orbitofrontal cortex of PE patients 43 .…”
Section: Discussionsupporting
confidence: 59%
“…The precuneus has been identified as hub regions in the brain of ED and PE patients, which were essential for the information integration of the brain 36‐38 . The superior temporal gyrus and supramarginal gyrus were two components of AUD, 39,40 and the superior temporal gyrus was one of the hubs in the brain network of PE patients 36 . Increased activities of the supramarginal gyrus and precuneus were observed in PE patients 26,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical images were performed with T1 weighted 3D sagittal acquisition (repetition time (TR), 1900 ms; echo time (TE), 2.48 ms; slice thickness, 1 mm; matrix size, 256 × 256; field of view (FOV), 250mm 2 × 250mm 2 ; flip angle (FA), 9°; slice thickness, 1 mm) [22] . The whole-brain diffusion MRI sequence using diffusion tensor spin echo planar imaging was acquired (TR, 6600 ms; TE, 93 ms, matrix size,128 × 128; FOV, 240mm 2 × 240mm 2 ; thickness, 3 mm; number of slices, 45).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%